Responsible, sustainable, and globally aware management in the fourth industrial revolution - Fields, Ziska, 1970-; Huesig, Stefan, 1972- (Business Science Reference, 2019)
"This book addresses different aspects of responsible, sustainable and globally aware management principles and practices to enable managers to use the changes that the Fourth Industrial Revolution creates strategically. It also provides the resources necessary for governments, nonprofit and for-profit organizations, and managers specifically to address sustainability needs in businesses and countries around the world"--